2021
DOI: 10.3390/catal11080997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ion-Exchange Sequences on Catalytic Performance of Cerium-Modified Cu-SSZ-13 Catalysts for NH3-SCR

Abstract: Cerium-modified Cu-SSZ-13 catalysts were prepared by an aqueous ion-exchange method, and Ce and Cu were incorporated through different ion-exchange sequences. The results of NH3-SCR activity evaluations displayed that Cu1(CeCu)2 catalyst presented excellent catalytic activity, and over 90% NOx conversion was obtained across the temperature range of 200–500 °C. The characterization results showed that the ion-exchange sequence of Cu and Ce species influenced the crystallinity of the zeolites and the coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Thereafter, Usui et al (2018) reported the Ce-incorporated Cu-SSZ-13 exhibited excellent hydrothermal stability since Ce located in the CHA cage of SSZ-13 could fill the defect sites, reduce the number of available attacks positions and stabilize the zeolite structure ( Figure 6C ). The introduced Ce could change the location and coordination environment of Cu 2+ ions and participate in the reaction process, which was beneficial for the low-temperature SCR activity ( Wang Y. et al, 2021 ). In the case of one-pot synthesized Cu-SSZ-13, the catalytic activity and sulfur resistance could be enhanced by modifying with Ce using the IE method ( Li et al, 2019 ).…”
Section: Introducing the Heteroatoms Or Metal Oxidesmentioning
confidence: 99%
“…Thereafter, Usui et al (2018) reported the Ce-incorporated Cu-SSZ-13 exhibited excellent hydrothermal stability since Ce located in the CHA cage of SSZ-13 could fill the defect sites, reduce the number of available attacks positions and stabilize the zeolite structure ( Figure 6C ). The introduced Ce could change the location and coordination environment of Cu 2+ ions and participate in the reaction process, which was beneficial for the low-temperature SCR activity ( Wang Y. et al, 2021 ). In the case of one-pot synthesized Cu-SSZ-13, the catalytic activity and sulfur resistance could be enhanced by modifying with Ce using the IE method ( Li et al, 2019 ).…”
Section: Introducing the Heteroatoms Or Metal Oxidesmentioning
confidence: 99%